Life lessons with Uramichi Oniisan. 4 - Kuze, Gaku (Kodansha Comics, 2023)
"How did the cynical Uramichi end up hosting a TV show for small children? And how long is the studio going to let him keep teaching the kids the sorrow and exhaustion of life instead of, say, the ABCs? This dark comedy manga started as a webcomic and became a bestseller across Japan -- now a hit anime! Time comes for us all--including URAMICHI's poor back muscles. While contending with an aging body and brutally honest kids may all be in a day's work for him, dealing with a happy-go-lucky con artist sure isn't! As URAMICHI is unwillingly dragged into another one of HANBEI's desperate attempts to meet upper management at the bare minimum, MITSUO and HACHITA are standing by to help with pure disinterest and an onslaught of painful truths"--